Hydridoorganostannylene Coordination: Group 4 Metallocene Dichloride Reduction in Reaction with Organodihydridostannate Anions. Issue 70 (13th November 2019) - Maudrich, Jakob‐Jonathan; Widemann, Max; Diab, Fatima; Kern, Ralf H.; Sirsch, Peter; Sindlinger, Christian P.; Schubert, Hartmut; Wesemann, Lars
Abstract: Organodihydridoelement anions of germanium and tin were reacted with metallocene dichlorides of Group 4 metals Ti, Zr and Hf. The germate anion [Ar*GeH2 ] − reacts with hafnocene dichloride under formation of the substitution product [Cp2 Hf(GeH2 Ar*)2 ]. Reaction of the organodihydridostannate with metallocene dichlorides affords the reduction products [Cp2 M(SnHAr*)2 ] (M=Ti, Zr, Hf). Abstraction of a hydride substituent from the titanium bis(hydridoorganostannylene) complex results in formation of cation [Cp2 M(SnAr*)(SnHAr*)] + exhibiting a short Ti–Sn interaction. (Ar*=2, 6‐Trip2 C6 H3, Trip=2, 4, 6‐triisopropylphenyl). Abstract : Reaction of metallocene dichlorides with anions of deprotonated organoelement trihydrides of germanium and tin affords substitution products or reduction followed by hydridoorganostannylene coordination.